Efficient removal of antibiotic in single and binary mixture of nickel by electrocoagulation process: Hydrogen generation and cost analysis - Oladipo, Akeem Adeyemi; Mustafa, Faisal Suleiman; Ezugwu, Obinna Nestor; Gazi, Mustafa (Pergamon-Elsevier Science Ltd, 2022)
In discharged water, antibiotics and heavy metals frequently coexist, forming stable and recalcitrant complexes. Environmental concerns about how to efficiently treat this type of pollution are growing. Using Fe and Al electrodes, electrocoagulation (EC) was applied to remove tetracycline (TC) as a single pollutant as well as TCnickel ions in a binary mixture from water. The effects of critical variables and the TC-Ni molar ratio (1:1, 1:2, and 2:1) were studied. The Fe electrode achieved 99.3% TC removal after 60 min in a single pollutant system containing 15 mgL(-1) of TC, while the Al electrode achieved 99.8% removal in 20 min at optimal conditions. The EC process demonstrated excellent electrodegradation efficiency towards TC-Ni complexes. When the TC to Ni2+ ratio was 1:1 and 1:2, respectively, TC elimination was 100% in 10 min and 99.6% in 20 min. We noted that a sufficient amount of Ni2+ could increase TC decomposition by electrocatalysis. The amount of hydrogen gas produced after treatment of a 0.2 L TC solution alone is 22.2-13.99 mol m(-3), whereas it was 27.2-40.8 mol m- 3 in the TC-Ni binary mixture, which can generate more than 35% of the electrical energy needed to power the EC system. To evaluate the generated sludge, FTIR analysis was performed.
Keywords: Electrocoagulation method; Emerging contaminants; Binary pollutant mixture; Electrodegradation; Hydrogen generation